2013
DOI: 10.1111/jocn.12235
|View full text |Cite
|
Sign up to set email alerts
|

Training of nurses in point‐of‐care testing: a systematic review of the literature

Abstract: Nurses can be trained using a variety of methods in different healthcare settings. To save resources, especially in large hospitals and sparsely populated areas, distance learning is worth considering. However if training is delivered with the support of laboratory professionals, nurses subsequently perform good-quality point-of-care testing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 30 publications
(62 reference statements)
2
16
0
Order By: Relevance
“…The POC curriculum we designed fills gaps in public health education and attempts to initiate a dialogue leading to availability of POC-enabled public health practitioners worldwide. We found only one educational article intended for “health professional students” (at the University of Zimbabwe College of Health Sciences), (14) one for “training of nurses,” (15) and one for OB-GYN residents (16) that were relevant to POCT. Another group addressed internet-based interactive education as a potential venue for education, but not specifically public health (17).…”
Section: Discussionmentioning
confidence: 99%
“…The POC curriculum we designed fills gaps in public health education and attempts to initiate a dialogue leading to availability of POC-enabled public health practitioners worldwide. We found only one educational article intended for “health professional students” (at the University of Zimbabwe College of Health Sciences), (14) one for “training of nurses,” (15) and one for OB-GYN residents (16) that were relevant to POCT. Another group addressed internet-based interactive education as a potential venue for education, but not specifically public health (17).…”
Section: Discussionmentioning
confidence: 99%
“…10 In most cases, the training of professionals is characterized by the transmission of knowledge, following the logic of banking conception in which the intention is to transmit information in a way that the educator places himself as the holder of the knowledge to be assimilated by the student. [2][3][4][7][8][9][10][13][14][15][16][17][18][19] In this context, accumulated experience and assessments over decades have shown that the mere transmission of content and the theory taught through training are seldom put into practice and therefore do not achieve the expected results. [10][11][19][20] Many motives can permeate as obstacles to achieving desired results, as presented in Article IV when they speak of the management of resources destined to the National Policy of CEH as an important factor.…”
Section: Continuous Education In Health and The Paulo Freire's Methodsmentioning
confidence: 99%
“…14 Fragments from the analyzed articles were inserted in order to support the discussions in the categories. The fragments were edited, without changing the content, in order to extract from the articles their core.…”
mentioning
confidence: 99%
See 2 more Smart Citations